E-Learning and Literacy: An Investigation into the Impact of Actively Learn to Raise Reading Comprehension Levels of High School Students - Jeffries, Fiona Grace Carter (Curtin University, 2020)
Fiona Jeffries’ research investigated the effect of the online platform Actively Learn in the development of reading comprehension skills of high school students. The study provided a model that synthesised student agency and autonomy, connectedness, and the centrality of the teacher’s role in the expansion of metacognitive skills to support reading comprehension.